IMPROVING THE DIAGNOSIS OF INTRAUTERINE INFECTION IN NEWBORNS BASED ON THE ASSESSMENT OF THE CYTOKINE SYSTEM - Людмила Алексеевна Кривцова; Татьяна Николаевна Белкова; Татьяна Владимировна Оксеньчук; Мария Александровна Плеханова; Юлия Игоревна Тирская (Мать и дитя в Кузбассе, 2020)
Currently, the problem of intrauterine infection (IUI) does not lose its relevance due to persistent peri- and postnatal losses, as well as the development of serious consequences in children, often leading to disability and a decrease in their quality of life. In this regard, it is important to study modern diagnostic criteria for intrauterine infection